2020
DOI: 10.3390/atmos11101130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate Variability on Soybean Yield in MATOPIBA, Brazil

Abstract: The objective of this study was to analyze the influence of large-scale atmospheric–oceanic mechanisms (El Niño–Southern Oscillation—ENSO and the inter-hemispheric thermal gradient of the Tropical Atlantic) on the spatial–temporal variability of soy yield in MATOPIBA. The following, available in the literature, were used: (i) daily meteorological data from 1980 to 2013 (Xavier et al., 2016); (ii) (chemical, physical, and hydric) properties of the predominant soil class in the area of interest, available at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
11

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 104 publications
2
17
0
11
Order By: Relevance
“…The magnitude of the environmental and GEIs effects showed that the test environment had a signi cant effect on grain yields. Differences in rainfall, humidity, and light in each environment during the experiment had a signi cant effect on soybean grain yields 15 . In this study, the Ngawi (2017) had the highest average grain yield (2.54 t/ha) compared to other environments.…”
Section: Discussionmentioning
confidence: 98%
“…The magnitude of the environmental and GEIs effects showed that the test environment had a signi cant effect on grain yields. Differences in rainfall, humidity, and light in each environment during the experiment had a signi cant effect on soybean grain yields 15 . In this study, the Ngawi (2017) had the highest average grain yield (2.54 t/ha) compared to other environments.…”
Section: Discussionmentioning
confidence: 98%
“…A low soybean yield results from a reduction in water availability during the reproductive periods, especially during the pod-filling period. This relationship highlights the importance of adjusting the sowing date to the current meteorological scenario in order to optimize production according to the water deficit pattern in the region [36].…”
Section: Climate and Soybean Yieldmentioning
confidence: 99%
“…Climate conditions specific for each cultivating year had the most effect on soybean yield [36]. In 2017, there were favorable conditions of temperature and humidity for the vegetative stages of soybean and yield (Table 4).…”
Section: Climate and Soybean Yieldmentioning
confidence: 99%
“…In addition, forest degradation has become a more important driver of carbon losses than deforestation 43 , including irrecoverable carbon stores within the Amazon basin 44 . Changes in MATOPIBA's re regime resulting from rapid land expansion are still poorly understood, but it is suggested that climate is also playing a relevant role in this region 9,45 , which could put at risk both food production and EAC biome stability. We investigated this possibility, using 40 years of climate data to test for evidence of an intensi cation of hydro-climatic trends over the EAC.…”
Section: Introductionmentioning
confidence: 99%